Assessment of Water Resource Sustainability and Glacier Runoff Impact on the Northern and Southern Slopes of the Tianshan Mountains - He, Qingshan; Yang, Jianping; Zhao, Qiudong; Chen, Hongju; Wang, Yanxia; Wang, Hui; Wang, Xin (Sustainability, 2025)
Water resources are vital for sustainable development in arid regions, where glacial runoff plays a significant role in maintaining water supply. This study quantitatively assesses the sustainability of water resources in the Manas River Basin (MnsRB) and the Muzati River Basin (MztRB), situated on the northern and southern slopes of the Tianshan Mountains, respectively, over the period from 1991 to 2050. Freshwater availability was simulated and projected using the Variable Infiltration Capacity Chinese Academy of Sciences (VIC-CAS) hydrological model. Furthermore, three development modes—traditional development, economic growth, and water-saving—were established to estimate future water consumption. The levels of water stress were also applied to assess water resources sustainability in the MnsRB and MztRB. Results indicate that from 1991 to 2020, the average annual available freshwater resources were 13.94 × 108 m3 in the MnsRB and 14.27 × 108 m3 in the MztRB, with glacial runoff contributing 20.24% and 65.58%, respectively. Under the SSP5-8.5 scenario, available freshwater resources are projected to decline by 10.94% in the MnsRB and 4.37% in the MztRB by 2050. Total water withdrawal has increased significantly over the past 30 years, with agriculture water demand accounting for over 80%. The levels of water stress during this period were 1.14 for the MnsRB and 0.87 for the MztRB. Glacial runoff significantly mitigates water stress in both basins, with average reductions of 21.16% and 69.84% between 1991 and 2050. Consequently, clear policies, regulations, and incentives focused on water conservation are vital for effectively tackling the increasing challenge of water scarcity in glacier-covered arid regions.